Food security, food waste and food sharing: The conceptual analysis - V. V. Bakharev; G. Yu. Mityashin; T. V. Stepanova (Пищевые системы)
Authors emphasize that food in the modern world is becoming less accessible due to the present global economic, geopolitical and climatic situation. At the same time a large share of food produced in the world goes to waste. It means that there is a need to implement tools that could provide people with access to food and reduce amount of food waste. Food sharing, a novel tool of collaborative food consumption, can be used to solve this problem. The paper introduces the concept of distributive food sharing and describes its different types. A description of the present state of distributive food sharing in Russia. We state that the environment for development of distributive food sharing in Russia is not favorable. The main conclusion of the article is the need to create conditions for the development of the concept of food sharing to provide those in need with food and minimize waste.